Comparative Evaluation of Physicochemical Properties of Some Commercially Available Brands of Metformin Hcl Tablets in Lagos, Nigeria - Akinleye M. Olusola, Adelaja I. Adekoya, Odulaja J. Olanrewaju (Journal of Applied Pharmaceutical Science)
There are several generics of metformin hydrochloride tablets available within the drug delivery system globally. Availability of numerous brands of Metformin tablets in Nigerian drug market today places health practitioners in a dilemma of generic substitution. The objective of the study was to determine the biopharmaceutical and chemical equivalence of eight brands of Metformin tablets marketed in Nigeria using in vitro tests. The physicochemical equivalence of eight brands of Metformin hydrochloride tablets were assessed through the evaluation of both official and non-official standards such as uniformity of weight, friability, hardness, disintegration, Assay and dissolution rate. All the brands complied with the official specifications for uniformity of weight, disintegration and dissolution tests. Brand B and C had the highest and lowest crushing strength respectively. However, for the friability test, one of the eight brands failed to meet the British pharmacopoeia specification for friability. Seven brands had values within the range specified for assay in the BP while Brand G failed the test. Only brand F, G and H met the BCS biowaiver criteria for very rapidly or rapidly dissolving tablets. Of all the eight brands evaluated in this study, only four brands could be regarded as being biopharmaceutically and chemically equivalent and therefore can be interchanged in the clinical practice.
Keywords: Metformin hydrochloride, physicochemical equivalence, quality, dissolution test, Biowaver.